MSME Empowerment Through Business Coaching Programs and Massive Online Open Course - Herdiana Dyah Susanti; Dian Arief Pradana; Moh. Fahrurrozi; Mahfud (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The impact of the COVID-19 pandemic has hit various sectors, including micro, small and medium enterprises (MSMEs). To stop the spread of this pandemic, many activities have been restricted under massive social restriction programs. Founded in 2015 and focused on empowering his MSMEs in Banyuwangi district and surrounding areas, Banyuwangi Untag Incubitek is committed to helping MSMEs to deal with this disease. Banyuwangi Untag Incubitek plays a role in helping MSMEs by working with mentors, coaches, financial institutions, government agencies and even foundations dedicated to his MSME development. His MSMEs who participate in this program include students, alumni and the general public. Gain the knowledge and skills to build and improve your existing business. The technique used in this empowerment program is to provide online coaching via Zoom platform, Untag Banyuwangi's Learning Management System "LMS". It is also available through Untag Banyuwangi's Massive Open Online Courses (MOOCs). The benefits of the coaching program that partners of this program can receive are various services in the field of entrepreneurship, and results such as increased sales from an economic point of view and job creation from a social point of view can be obtained. surrounding community. In addition to knowledge and insight, he is evolving to be able to motivate his MSME stakeholders with businesses affected by the pandemic to innovate further.